The code of life : all about genes, DNA, genetic engineering, and why you are the way you are - Häfner, Carla, 1978- (Flying Eye Books, 2024)
"This book explains genetic theory, what genes are, why DNA plays an important role and what all these insights have to do with a curious monk. An exciting journey through the history of science, present-day genetic research and engineering and right through to the question of identity--because who would have thought how much of our personality is defined by our genes and how interesting genes can be?"--